Pre-drying optimization of oil palm veneers by response surface methodology - Abd Halip, Juliana; Ibrahim, Azmi; Abdan, Khalina; Bakar, Edi Suhaimi; Karimi, Alinaghi; M. Tahir, Paridah; Choo, Adrian Cheng Yong (Springer, 2015)
For the manufacture of veneers, oil palm trees are considered as a suitable alternative material to traditional woods such as rubberwood and meranti. However, the high moisture content (MC) in oil palm wood is a major barrier for processing. Response surface methodology was used to optimize the oil palm pre-drying process. Oil palm veneers were fed into a veneer roller press machine to squeeze out moisture by varying passes, pressure and roller speed. For the outer oil palm veneers, pre-drying was carried out with 2 passes at a pressure of 8042 kPa and speed of 41.49 Hz. Optimum conditions for the inner oil palm veneers were found at 2 passes, a pressure of 7550 kPa and speed of 41.49 Hz. The MC reduction was determined at 17.62 % for the outer and 22.01 % for the inner veneers. In conclusion, pre-drying treatment significantly reduces the moisture content of oil palm veneers and lowers drying time.